2005
DOI: 10.1186/1746-6148-1-8
|View full text |Cite
|
Sign up to set email alerts
|

ATP-sensitive potassium channel (KATPchannel) expression in the normal canine pancreas and in canine insulinomas

Abstract: Background: Pancreatic beta cells express ATP-sensitive potassium (K ATP ) channels that are needed for normal insulin secretion and are targets for drugs that modulate insulin secretion. The K ATP channel is composed of two subunits: a sulfonylurea receptor (SUR 1) and an inward rectifying potassium channel (Kir 6.2 ). K ATP channel activity is influenced by the metabolic state of the cell and initiates the ionic events that precede insulin exocytosis. Although drugs that target the K ATP channel have the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Proton leak activity of UCP2 has an important role in negative regulation of insulin secretion via its inhibition of ATP synthesis in b-cells (Jezek 2002). Pancreatic endocrine b-cells are glucose-sensing cells equipped with a K ATP channel consisting of two subunits, SUR1 and Kir6.2 (Donley et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Proton leak activity of UCP2 has an important role in negative regulation of insulin secretion via its inhibition of ATP synthesis in b-cells (Jezek 2002). Pancreatic endocrine b-cells are glucose-sensing cells equipped with a K ATP channel consisting of two subunits, SUR1 and Kir6.2 (Donley et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…6 The relationship between GCK and HK1 gene expression in insulinoma has not been reported previously in any species, and information about expression of other genes involved in glucose metabolism by insulinomas is scant. [13][14][15] We found that the insulinoma overexpressed GCK compared with normal pancreatic tissue from the same cat, but HK1 expression was nearly equivalent in both tissues. Comparison of GCK expression in tumor and feline islets might have provided additional information.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium channels play an important role in regulating insulin secretion from the beta cells of the pancreas. Pancreatic beta cells express ATP-sensitive potassium (KATP) channels that are needed for normal insulin secretion and are targets for drugs that modulate insulin secretion [ 37 ]. When glucose levels are high, glucose enters the beta cells and triggers a series of events that lead to the opening of potassium channels.…”
Section: Antidiabetic Medicationsmentioning
confidence: 99%